Trends in trauma care before and after the introduction of ‘Mukhyamantri Santwana Harish Scheme’ in a tertiary care hospital at Kolar - Kottareddygari, Vikas Sankar; S., Vishwas; G. P., Praveen; Abraham, Amal; P. N., Sreeramulu (International Journal Of Community Medicine And Public Health, 2018)
Background: Road traffic injuries (RTI) are responsible for 1.2 million global deaths and rank 9th as cause of death in both the high and low income countries. Polytrauma cases make the bulk of emergencies in our centre and the victims were previously given only first aid and critical care before being referred to a government aided institute for further management due to monetary issues. After the introduction of Mukhyamantri Santwana - 'Harish' Scheme (MSHS), all the patients are entitled for cashless treatment for the first 48 hoursand this improved the quality of care they received. Methods: All the polytrauma cases brought to the emergency and critical care department for a period of 7months before the introduction of MSHS (October 2015- April 2016) and for a period of 7 months from the introduction of MSHS (May 2016- November 2016) were studied retrospectively. Data on the number of patients referred, admitted and underwent intervention during the time periods were collected and compared. Results: The number of cases that were admitted and given intervention in our centre increased considerably and number of cases referred to other centres decreased after the introduction of MSHS. Conclusions: Introduction of MSHS lead to patients receiving more advanced life support and interventions as necessary. However this cannot be generalised to all the centres as data is still lacking. Multicentric studies need to be done in this aspect.